Comparison of simple and continuous construction with restrained and unrestained beam design using steel grade s275 [electronic resource] - 351587 Prem Rakesh Kervsseben; Fakulti Kejuruteraan Awam (2009)
Project Paper (Sarjana Muda Kejuruteraan (Awam - Struktur dan Bahan)) - Universiti Teknologi Malaysia, 2009